2014
DOI: 10.1080/17290376.2014.938103
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of HIV-related stigma among HIV-positive older persons in Uganda – a mixed methods analysis

Abstract: There is limited data on stigma among older HIV-infected adults in sub-Saharan Africa. We describe the experiences of stigma and disclosure in a cohort of HIV-positive older people in Uganda. Using data from the Wellbeing of Older Peoples' Study of Kalungu (rural site) and Wakiso district (peri-urban site) residents, we measured self-reported stigma levels for 183 respondents (94 on antiretroviral therapy (ART); 88, not on ART) using a stigma score generated using three questions on stigma perceptions where 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 32 publications
4
32
1
1
Order By: Relevance
“…Findings from our study indicate that several years into the HIV epidemic, stigma is still a challenge and more so to older adults, confirming findings from other studies [12,13,45,46]. Compared to younger adults, older adults living with HIV face double stigmathe stigma attached to HIV infections, and the stigma attached to engaging in sex at an older age.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Findings from our study indicate that several years into the HIV epidemic, stigma is still a challenge and more so to older adults, confirming findings from other studies [12,13,45,46]. Compared to younger adults, older adults living with HIV face double stigmathe stigma attached to HIV infections, and the stigma attached to engaging in sex at an older age.…”
Section: Discussionsupporting
confidence: 87%
“…More than three decades into the HIV epidemic, stigma and discrimination towards persons infected with HIV continue to persist. Older persons living with HIV experience stigma related to HIV [12] and discrimination due to age [13]. In some cases, older persons have been branded too old to be HIV infected [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among HIV-positive older adults, “positive prevention” campaigns with intensified counseling and motivation about sexual transmission risks should be considered, 45,46 with attention to HIV-related stigma that may be experienced by older adults. 47,48 Specific programs ensuring universal HIV testing, rapid linkage of HIV-positive people to care, and supported HIV treatment retention and adherence should also be considered. 17,49 Among HIV-negative older adults, it will be important to consider how established interventions, such as medical male circumcision 50 and condom promotion, and novel interventions, such as preexposure prophylaxis, 18 can be designed and delivered in ways that best meet the needs of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that about two-thirds of all respondents fear the consequences of revealing HIV+sero status (Kuteesa et al, 2014). The findings from this study were similar to several studies in Africa found that AIDS epidemic has often been associated with severe negative public reactions ranging from banning entry of HIV infected individuals to isolating an individual in the family, deserting a pregnant wife on knowing her HIV status in the hospital, or removing a person from his job, or even denying a child admission in school.…”
Section: Discussionmentioning
confidence: 78%